2014
DOI: 10.1016/j.bjid.2013.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality in burn children

Abstract: In this series of burn children age ≤ 4 years, Garces index score 4, colistin use in documented multiresistant infections, mechanical ventilation and graft requirement were identified as independent variables related with mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 25 publications
2
26
0
3
Order By: Relevance
“…This finding is consistent to the previous pediatric burn studies, 61,82 . 55,54,83,84 It is important, to report hospital mortality rate that relate to TBSA burnt.…”
Section: Mortalitysupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent to the previous pediatric burn studies, 61,82 . 55,54,83,84 It is important, to report hospital mortality rate that relate to TBSA burnt.…”
Section: Mortalitysupporting
confidence: 93%
“…This finding is in agreement with the most of previous studies. 61,89,90 The highest level of death caused by infection is probably due to the lack of early wound swab and blood culture for bacteria and sensitivity of organism which is leading to septicemia and then death. Furthermore, a study by Ramakrishnan, M., et al showed that early management and empirical antibiotic regimes decrease wound sepsis resulting to the increase of survival.…”
Section: Mortalitymentioning
confidence: 99%
“…Similarly, Rosanova et al also determined that mechanical ventilation was an independent variable related to mortality in children with burns. [15] Queiroz et al also reported that mechanical ventilation requirement was associated with significantly increased mortality rate in burn victims. [5] These results were also compatible with our findings.…”
Section: Discussionmentioning
confidence: 94%
“…1 A pesar de los avances en el cuidado del paciente quemado, las infecciones continúan siendo una causa fundamental de morbimortalidad en estos pacientes, debido al daño en la integridad de la barrera cutánea y al compromiso del sistema inmune, son una complicación frecuente en los pacientes hospitalizados por lesión térmica. [2][3][4] El diagnóstico y tratamiento oportuno de la infección están asociados con una mejor evolución, de allí la importancia de disponer de marcadores precoces. El tiempo de tratamiento en estos pacientes no está definido con claridad, por lo que un parámetro de seguimiento de la respuesta inflamatoria sería potencialmente útil para las decisiones terapéuticas.…”
Section: Introductionunclassified